Dear God, It's Me Again - Annie Fitzgrald (Grand Rapids, United States Flying Frog Publishing, 2003)
Annie Fitzgerald's popular art and Ken Abraham's expert insights give kids answers to the real questions they most want to ask God. This beautifully written and uniquely illustrated series helps to answer the profound and sometimes complex questions children want to ask God about themselves, their world, and God himself. The answers are written to help children understand and to help adults engage kids in meaningful discussion. Dear God . . . If I gave all my love away . . . could I have a refill? Dear God . . . You should have asked me if I wanted freckles. Dear God . . . I'm tired of sitting on the side. Dear God . . . I need to make some big decisions. Can we talk? Dear God . . . Do you have any problems?
Keywords: EY - RM -- EY - RM